Adsorption and Kinetic Study on Sn2+ Removal Using Modified Carbon Nanotube and Magnetic Biochar - Mujawar, Mubarak; Ruthiraan, M.; Sahu, J.; Abdullah, E.; Jayakumar, N.; Sajuni, N.; Tan, J. (2013)
The effectiveness of stannum (Sn 2+ ) removal from aqueous solution by using magnetic biochar and functionalized multiwalled carbon nanotube (FMWCNT) was investigated. The effect of various factors, namely pH, adsorbent dosage, agitation speed and contact time was statistically studied through analysis of variance (ANOVA). Statistical analysis revealed that the optimum conditions for the highest removal of Sn 2+ are at pH 5, dosage 0.1 g with agitation speed and time of 100 rpm and 90 min, respectively. At the initial concentration of 0.1 mg/L, the removal efficiency of Sn 2+ using FMWCNTs was 93% and 85% with magnetic biochar. The Langmuir and Freundlich constant for both FMWCNTs and magnetic biochar were 13.397 L/mg, 18.634 L/mg and 17.719 L/mg, 25.204 L/mg, respectively. Hence, results prove that FMWCNTs are a better adsorbent with a higher adsorption capacity compared to magnetic biochar. Adsorption kinetic obeyed pseudo-second-order.